TINJAUAN YURIDIS TERHADAP PAJAK PENGHASILAN ATAS USAHA JASA KONSTRUKSI - Muhammad Yasid; Hang Bun (JURNAL RECTUM: Tinjauan Yuridis Penanganan Tindak Pidana, 2020)
Taxes are a very important source of state revenue for administering government and implementing national development. So that the Government places taxation obligations as one of the manifestations of state obligations which are a means of financing the state in national development in order to achieve the goals of the State. This research uses a normative method, which is to analyze problems and research through an approach in statutory regulations and also from books, papers, laws and other references. The construction service business is a tax object subject to final Income Tax (PPh) of Article 4 paragraph (2). In the construction service business, the construction service contractor or entrepreneur is subject to tax. This applies to both those who have and who do not have certification and qualifications as professionals in the construction sector in accordance with the provisions stipulated in the Construction Services Development Agency (LPJK) Regulation Number 11 of 2006. The legal umbrella governing taxes on construction service businesses is listed in Government Regulation (PP) Number 51 of 2008 as amended by Government Regulation Number 40 of 2009 concerning Income Tax on Income from Construction Services Business (hereinafter referred to as PP 51/2008 stdd PP 40/2009).